International consensus principles for ethical wildlife control - Sara Dubois; Nicole Fenwick; Erin A. Ryan; Liv Baker; Sandra E. Baker; Ngaio J. Beausoleil; Scott Carter; Barbara Cartwright; Federico Costa; Chris Draper; John Griffin; Adam Grogan; et al. (Conservation Biology, 2017)
Human–wildlife conflicts are commonly addressed by excluding, relocating, or lethally controlling animals with the goal of preserving public health and safety, protecting property, or conserving other valued wildlife. However, declining wildlife populations, a lack of efficacy of control methods in achieving desired outcomes, and changes in how people value animals have triggered widespread acknowledgment of the need for ethical and evidence‐based approaches to managing such conflicts. We explored international perspectives on and experiences with human–wildlife conflicts to develop principles for ethical wildlife control. A diverse panel of 20 experts convened at a 2‐day workshop and developed the principles through a facilitated engagement process and discussion. They determined that efforts to control wildlife should begin wherever possible by altering the human practices that cause human–wildlife conflict and by developing a culture of coexistence; be justified by evidence that significant harms are being caused to people, property, livelihoods, ecosystems, and/or other animals; have measurable outcome‐based objectives that are clear, achievable, monitored, and adaptive; predictably minimize animal welfare harms to the fewest number of animals; be informed by community values as well as scientific, technical, and practical information; be integrated into plans for systematic long‐term management; and be based on the specifics of the situation rather than negative labels (pest, overabundant) applied to the target species. We recommend that these principles guide development of international, national, and local standards and control decisions and implementation.